KONTEKSTUALISASI SURAT AL-KAHFI AYAT 66-82 DALAM PENDIDIKAN KONTEMPORER - Ana Rahmawati (Universitas Islam Nahdlatul Ulama Jepara, 2016)
ABSTRCTIn shaping the child's personal or character, not as easy as turning the palm of the hand. Therefore through private education is good will be created or attached to the child??s soul. Beberapa methods used among other methods of customs, ideals and others. Now we see the phenomenon of smearing ethics in our education, both came from educators and learners, as Muslims we have been taught by the Koran on ethics and procedures for good learning. By digging the Koran in a letter al-Kahf verse 66-82 will unfold the moral teaching contained in these verses that can be implemented in education today. The roles and responsibilities of an educator is very heavy. Especially in the context of Islamic education, where all aspects of education in Islam is linked to values, to which see teachers not only on mastery of material knowledge, but also the cultivation of moral values and spiritual which is then transformed towards the formation of the personality of students. As the most basic component in Islam, educators are required to guide, train and familiarize the students to always behave well. Therefore, the existence of educators not only teach, but once put into practice the teachings and values of the teaching of Islam. Keywords : Islamic education, al-Qur??an, student and aducators.